Guilty (or invisible) materiality in everyday object relations? - Green, Clare; Treilhou, Stéphane (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
In today’s context, demanding radical change even on the scale of our daily behaviour, this article builds on research into guilty materiality to better understand obstacles to changing our everyday material relations. “Guilty materiality“ refers to why materiality and material relations may be stigmatised, invisibilised, ignored and avoided. Daily material relations self-documented by 82 university-level design students provide the tangible basis for exploring and highlighting obstacles and ambiguities in daily-life artefact relations and their materiality. Our study focuses only on what is touched by the cohort, constituting a limited number of artefact encounters. The main analysed material is individual maps produced by students visualising their daily consumption habits. While the long-term aim of this research is to help identifying leverage points and action areas related to current practices and also mindsets, this paper also presents and explores the pertinence of the proposed methodology in this context. This research discusses, refines and adds to an existing list of triggers/influencing mechanisms that may act as obstacles to more environmentally-relevant everyday material relations.